Corporate Social Responsibility As An Instrument Of Peace Between The Multinational Oil Companies And The Niger Delta, Nigeria - Amos Ojo Adedeji Ph.D (International Journal of Business and Quality Research, 2023)
Corporate Social Responsibility came into limelight in the early 20th century in the middle of growing concerns about the duties of organisation as the ideas of charity and stewardship. The paper examines effectiveness of corporate social responsibility as a strategy of peace between multinational oil firms and the host communities in Nigeria's Niger Delta. The work uses a content analysis approach and primarily draws on secondary sources. The paper found that deprivation and uneven distribution of the Niger Delta’s natural resources coupled with the failure of oil companies in their corporate social responsibility led to the crisis in the region. To improve the already strained relationships, the oil companies carried out developmental projects such as social and basic infrastructures, education, empowerment and healthcare among others. The study recommends people-centred development strategies, strict adherence to the principle of corporate integrity, protection of citizens against ill effects of oil activities by government and strong community participation in developmental projects. Effective and efficient management of the host community perceptions is also key.